Simulation of the Pressure Vessel Saddle Thickness Effect to Stress Distribution - Krisdiyanto Krisdiyanto (Universitas Sebelas Maret, 2021)
Cylinder pressure vessel is a device that is used to process industry, power industry, oil industry, and gas industry. Structure of pressure vessel has complex design that is used to accommodate force, temperature, internal pressure loading, etc. Pressure vessel loading is supported by two saddle. Loading pressure vessel is distributed to saddle as stress. Stress distribution can be checked by finite element software. Autodesk Inventor 2019 is a software that used finite element basic. This research aims to get the effect of pressure vessel saddle width to maximum stress at pressure vessel.